Simultaneous Determination of Multiple Acid-Suppressing Drugs by UPLC-MS/MS Method and Application for Pharmacokinetics Study - Li X; Liu S; Yu M; Xi W; Wu X; Liu D; Liu A; Wang H (Drug Design, Development and Therapy)
Xiuqi Li,1,* Shupeng Liu,1,* Mengyang Yu,1 Wanlin Xi,1 Xiaofei Wu,1 Dan Liu,2 Aijing Liu,1 Hongyun Wang1 1Clinical Pharmacology Research Center, Peking Union Medical College Hospital, NMPA Key Laboratory for Clinical Research and Evaluation of Drug, Beijing Key Laboratory of Clinical PK & PD Investigation for Innovative Drugs, Chinese Academy of Medical Sciences and Peking Union Medical College, Beijing, 100730, People’s Republic of China; 2School of Life Science and Biopharmaceuticals, Shenyang Pharmaceutical University, Shenyang, Liaoning, 110000, People’s Republic of China*These authors contributed equally to this workCorrespondence: Hongyun Wang, Email wanghy@pumch.cnBackground: Proton pump inhibitors (PPIs) and potassium competitive acid blockers (P-CABs) are widely used to treat acid-related diseases (ARDs). Precisely quantifying their plasma levels is crucial for clinical pharmacokinetic assessments and therapeutic drug monitoring.Aim: This study aimed to establish a generic and efficient ultra-performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) assay for the determination of five PPIs (esomeprazole, rabeprazole, ilaprazole, lansoprazole, and pantoprazole) and the P-CAB (vonoprazan) in human plasma.Methods: The six analytes were extracted from human plasma via protein precipitation and a single dilution step. Detection was performed on a triple quadrupole tandem mass spectrometer with positive electrospray ionization. Chromatographic separation was achieved on the ACQUITY UPLC BEH C18 column (2.1 × 50 mm, 1.7 μm) using gradient elution. The mobile elution was composed of 0.2% formic acid in acetonitrile (mobile phase A), 0.1% ammonium hydroxide and 10 mmol/L ammonium formate in deionized water (mobile phase B). The flow rate was 0.4 mL/min, the run time was 4.5 minutes, and the injection volume was 20 μL.Results & Conclusions: The method exhibited excellent linearity across the ranges of 0.2– 200 ng/mL for PPIs and 0.5– 500 ng/mL for the P-CAB. Both intra- and inter-day precision and accuracy were within the acceptance criteria, with precision ranging from 1.1% to 14.6% and accuracy ranging from 0.0% to 14.7%. Extraction recoveries were consistent, ranging from 88.1% to 96.7%, with no significant matrix effects observed. The stability of the six analytes under diverse storage and processing conditions was also confirmed, with both precision and accuracy falling within the acceptable range of 15%. The UPLC-MS/MS assay provided an efficient and reliable approach for the simultaneous determination of six acid-suppressing medications in a single analytical run. It has been successfully applied to the pharmacokinetic studies of PPIs and P-CABs, offering a valuable tool for clinical research and therapeutic drug monitoring.Keywords: acid-suppressing drugs, PPIs, P-CAB, UPLC-MS/MS